The ALPACA study: (In)Appropriate LAMA prescribing in asthma: A cohort analysis. (December 2021) - Baan, E.J.; Hoeve, C.E.; De Ridder, M.; Demoen, L.; Lahousse, L.; Brusselle, G.G.; Verhamme, K.M.C.
Abstract: Introduction: Since long-acting muscarinic antagonists (LAMA) are only indicated as add-on therapy in subjects with moderate-to-severe asthma, there are concerns whether LAMA monotherapy is associated with worse asthma control. Aim: To study the prevalence of LAMA monotherapy and its potential association with severe asthma exacerbations (SAE) in patients with asthma. Methods: A cohort study (2007–2017) in the IPCI primary care database, in asthma patients aged 6–50, using LAMA during follow-up. Respiratory prescriptions were retrieved from the electronic medical records based on ATC code. Asthma treatment periods were created and categorized as LAMA mono, dual (LAMA + ICS), or triple therapy (LAMA + ICS + LABA). Relative rates (RR) of SAE, adjusting for patient characteristics, were estimated to compare treatments. Results: From a total of 66, 508 asthma patients, 1236 (1.9%) LAMA users were identified. Median age was 41 years, 65.9% were females. LAMA users were responsible for 3596 LAMA treatment periods of which 1390 (38.7%) were LAMA monotherapy, 553 (15.4%) dual therapy and 1653 (46.0%) triple therapy. The RR of SAE during LAMA monotherapy compared to dual therapy was 1.5 (95% CI 0.6–3.8). In patients alternating between mono and dual therapy (but never triple therapy), the RR for LAMA monotherapy increased to 5.7 (95% CI 1.4–23.6). Conclusions: This observational study shows that when LAMA is prescribed, it is often prescribed without concurrent ICS (LAMA monotherapy). LAMA monotherapy was associated with an increased risk of exacerbations when not used concurrently with ICS. This emphasizes the importance that LAMA should never be prescribed without concomitant ICS use in patients with asthma. Highlights: LAMA therapy in asthmatic patients is often prescribed without concomitant ICS prescription. Of all patients prescribed LAMA monotherapy, 14% had experienced a severe asthma exacerbation in the year prior. LAMA monotherapy was associated with an increased risk of exacerbations when not used concurrently with ICS. This study emphasizes the importance of ICS prescription concomitant with LAMA prescriptions in patients with asthma.